Falling from Grace and the Problem of Free Will - Hassoun, Nicole (European journal for philosophy of religion, 2022)
On the traditional Christian doctrine: 1. People have free will (in Heaven as on Earth). 2. Those with free will can go to Hell. 3. Heaven is eternal. Many Christians also hold: 4. God is all powerful, knowing and good and 5. Free will can justify eternal suffering, evil, or hell. The paper argues that those who accept a version of Christianity that endorses 1-5 face a dilemma: Either deny that free will can justify suffering, evil, or hell or accept that we can fail in heaven and so go to hell. It suggests that compassionate Christians may do best to i) give up on the idea that free will is valuable enough to justify significant suffering. This may require: ii) accepting that something has gone woefully wrong on Earth and iii) giving up the idea that people can suffer significantly in Hell, but allows Christians to maintain that iv) Heaven is eternal.